Classification of Biomaterials used in Medicine - Patitapabana Parida; Ajit Behera; Subash Chandra Mishra (Institute of Advanced Engineering and Science, 2012)
In this decade many researches are potentially going forward by using biomaterials in the medical field. Biomaterials can used in living creature body, taking in account of there biocompatibility. This paper describes about classification of different biomaterials which are used in medical industries. Advances in surgical technique and instruments have permitted materials to be used in ways that were not possible previously. Bio-material can partially/totally replaces one or more part of the body. Before using biomaterials, it should in mind that, which categories they are belongs and main focuses are on biocompatibility, bioinert, bioactive/surface reactive, biodegradable, sterilizability, adequate mechanical and physical properties, manufacturability, low weight, reasonable cost etc. It is necessary to classify biomaterials for there suitable use in medical industries.